MODEL KEPRIBADIAN ISLAMMELALUI PENDEKATAN PSIKOSUFISTIK - Abdul Mujib (Nuansa : Jurnal Studi Islam dan Kemasyarakatan, 2015)
Through  psycho-Sufi  approach that  emphasizes the  taste  (dzawqiyah) and  purification  processes (tazkiyah  al-nafs),  the  Islamic  personality leads  to the  formation of the  human mind.  Model of Personality  in psychosufistic is more  focused on self-cleaning (tazkiyah  al-nafs)  of sin, so that more  clean  from sin and  evil person the better the personality. Certainly does not stop there, but until the filling themselves with good conduct and felt themselves to be spiritual majesty and love of God